HUBUNGAN PENGETAHUAN IBU NIFAS PRIMIPARA TENTANG TEKNIK MENYUSUI DENGAN KEJADIAN PUTING SUSU LECET DI PMB DIAN AWI ANNGRAENI - Hayuningsih, Sri; Taufik, Afifah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Nipple abrasions are a common complication in the lactation process, especially for primiparous postpartum mothers. This condition is often caused by the first experience of breastfeeding and a lack of knowledge about correct techniques. Objective: This study aimed to analyze the relationship between the knowledge of primiparous postpartum mothers about breastfeeding techniques and the incidence of nipple abrasions at PMB Dian Dwi Anggraeni. Methods: This research used a correlational analytical design with a cross-sectional approach. The sample consisted of 30 primiparous postpartum mothers. The independent variable was knowledge of breastfeeding techniques, and the dependent variable was the incidence of nipple abrasions. The data were analyzed using the Chi-Square statistical test. Results: The results showed that the majority of respondents had poor knowledge (18 respondents or 56%) and most experienced nipple abrasions (18 respondents or 60%). The Chi-Square test yielded a significance value (p-value) of 0.000, which is less than 0.05. Conclusion: There is a significant relationship between the knowledge of primiparous postpartum mothers about breastfeeding techniques and the incidence of nipple abrasions at PMB Dian Dwi Anggraeni. This indicates that low knowledge contributes to the high incidence of nipple abrasions